Pregnancy Anemia its Relation to Low Birth Weight (Lbw) Incidence - Fitriana Ikhtiarinawati Fajrin; Khusnul Nikmah; Lilik Darwati; Nining Istighosah (MultiTech Publisher, 2023)
Anemia is one of the major nutritional issues in Indonesia and a prevalent problem among pregnant women worldwide, with a relatively high incidence rate. Pregnant women are particularly susceptible to anemia because the increased nutritional requirements during pregnancy are crucial for both maternal health and fetal growth. Pregnancy-related anemia is defined as a hemoglobin (Hb) level less than 11 (g/dL) in the blood of pregnant women. This study aims to analyze the relationship between anemia and the occurrence of Low Birth Weight (LBW). The research was conducted in the VK Room of Sugio Primary Health Care, Lamongan Regency, over a period of 2 months in August-September 2023. The research method used was a Retrospective Observational Study with a Cross-Sectional design. Based on the Chi-Square statistical test results, the p-value was 0.025 (p-value < 0.05). In conclusion, this study found a significant association between anemia during pregnancy and the incidence of LBW.